2017
DOI: 10.1016/j.micinf.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lung eosinophil recruitment in response to Aspergillus fumigatus is correlated with fungal cell wall composition and requires γδ T cells

Abstract: The differential recognition of fungal cell wall polysaccharides that program innate and adaptive immunity to the human opportunistic fungal pathogen Aspergillus fumigatus has been a focus of considerable interest. In a mouse model of fungal conidia aspiration, decreased relative levels of cell wall core carbohydrates β-1,3-glucan to chitin in A. fumigatus isolates and mutant strains were correlated with increased airway eosinophil recruitment. In addition, an increase in fungal surface chitin exposure induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In this regard, deficiency in IL-17 or γδ T cells did not reduce A. fumigatus burden in the lung of mice [42,43]. Instead, lack of γδ T cells appeared to confer protection from pulmonary aspergillosis [42,43]. Humans with lack of functional NADPH oxidase suffer from chronic granulomatous disease (CGD), which is characterized by recurrent bacterial and fungal infections, including Aspergillus, as well as uncontrolled inflammation [8].…”
Section: Role Of γδT17 Cells In Infection Fungal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, deficiency in IL-17 or γδ T cells did not reduce A. fumigatus burden in the lung of mice [42,43]. Instead, lack of γδ T cells appeared to confer protection from pulmonary aspergillosis [42,43]. Humans with lack of functional NADPH oxidase suffer from chronic granulomatous disease (CGD), which is characterized by recurrent bacterial and fungal infections, including Aspergillus, as well as uncontrolled inflammation [8].…”
Section: Role Of γδT17 Cells In Infection Fungal Infectionsmentioning
confidence: 99%
“…In contrast to C. albicans , it appears that γδT17 cells are not required to protect against Aspergillus fumigatus . In this regard, deficiency in IL‐17 or γδ T cells did not reduce A. fumigatus burden in the lung of mice [42, 43]. Instead, lack of γδ T cells appeared to confer protection from pulmonary aspergillosis [42, 43].…”
Section: Role Of γδT17 Cells In Infectionmentioning
confidence: 99%
“…Monocyte‐derived macrophages and dendritic cells are often recruited into the airway . Likewise, other myeloid cell populations, including neutrophils, monocytes and eosinophils, infiltrate the airways in an effort to combat the infection. In almost all cases of pulmonary fungal infection, the development of adaptive immunity and the engagement of CD4 T‐cell help is a key determinant of the outcome on infection.…”
Section: Fungal Recognition and T‐cell Priming The Lungmentioning
confidence: 99%
“…Reese et al (2007) found chitin exposure in the airways to be associated with recruitment of IL-4-expressing innate immune cells, eosinophils, and basophils, along with an M2 macrophage phenotype in mice relative to a saline-challenged control ( Figure 3A). An increased chitin to bglucan expression ratio in A. fumigatus strains resulted in greater eosinophil recruitment in a mouse model of airway inflammation, dependent on gd-T cells, indicating the role of this T cell subset in the type 2 response to chitin (Amarsaikhan et al, 2017). Using Ccr1 -/mice, Blease et al (2000) showed that C-C Motif Chemokine Receptor 1 (CCR1) signalling is necessary for Th2 responses and airway remodeling in a A. fumigatus model of airway inflammation, another mechanism by which fungi are capable of eliciting such airway response.…”
Section: Fungal-mediated Immune Mechanisms In Asthmamentioning
confidence: 97%